Algumas notas sobre as transformacoes do comercio na regiao administrativa de Campinas. - Berrios, M. R.; Pintaudi, S. M. (My University, 1984)
Examines the relationship between commerce and distribution, consumption and production, before describing the spatial evidence of recent change in the commercial sector in the Campinas region, Chile. -R.N.Gwynne
(Some notes on the transformation of commerce in the administrative region of Campinas, Chile).